The "body politic" in ancient China - Huang, Chun-chieh (Acta Orientalia Vilnensia, 2007)
The ‘body politic’ occupies the core position in traditional Chinese political thinking. This is strongly supported by the fact that, for most ancient Chinese philosophers, self-cultivation was taken as the starting point of a programmatic way leading to the management of the world. The aim of this essay is to analyze the meaning and significance of the prevailing ‘body politic’ of ancient China.In section two, the Chinese ‘body politic’ is placed within a comparative frame with the ideas of Plato (428–347 BCE) and Hobbes (1588–1679). It is argued that the ‘body politic’ in China is far from an abstract or theoretical discourse; the state was epistemologically taken as an extension of the human body, which is integral and organic in itself. Thus the body served as a metaphor or symbol to explain the organization and functionality of the state.Section three details the ‘body politic’ in three ways. First, due to the comparability between the state and the body, the ruling of the state, as that of the body, should also commence with a kind of inside-out, morality-concerned self-cultivation. Second, there is a complicated interdependency between state functions, which are similar to those of the body. Third, if there is a center of dominancy gathered through the interactive process of the body, then a kind of political autocracy can thus be extrapolated in by the ‘body politic’.The conclusion points out that, in ancient Chinese body-thinking, the mind-heart had its socio-political dimensions, and the ‘body’ is no less than a psychosomatic one. Since the unification of China in 221 BCE, Confucianism had gradually gained the political vantage and become the imperial ideology. However, the ancient ideal of the ‘Confucianization of politics’ was thus transformed to the reality of the ‘politicization of Confucianism’.
Keywords: -